(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Dental caries is characterized by demineralization of inorganic portion of tooth and destruction of organic substances of tooth, which often leads to cavitation. The immune mechanisms play an important role in the pathogenesis of dental caries.This study was designed to determine the levels of salivary IgA, TGF-β and IL-17 in patients with dental caries. Methodology: This was a comparative study of 87 individuals (29 healthy controls and 58 patients with dental caries) recruited from the Punjab Dental Hospital, Lahore. Group I included patients with dental caries up to 5 DMFT score (Decayed Missing Filled Teeth), group II had patients with 6 or more DMFT score and group III consisted of healthy individuals without dental caries. Commercially available ELISA kits were used for the detection of salivary IgA, TGF β and IL-17. Results: Highest mean ± SD level of IL-17(2.99±1.11ng/L)and TGFβ (127.8 ±74.0ng/L) were detected in group III. While highest mean ± SD level of salivary IgA (μg/ mL) was detected in the group I (34.64±6.37μg/mL) Conclusion: Level of salivary IgA was increased in patients of dental caries while levels of IL-17and TGFβ were decreased in patients of dental caries as compared to healthy individuals. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.536-539